The Development of National Islamic Foreign Exchange Bank in Indonesia - Fatwa, Nur (Journal of Strategic and Global Studies, 2020)
Stagnation is a challenge faced by Islamic banking. Inadequate capital, small scale industries and banks, and low efficiency are the main obstacles to sharia banking in Indonesia. Therefore, the arrangement of various aspects needs to be done, so that national Islamic foreign exchange banks can compete with conventional commercial banks in terms of the effectiveness and efficiency of business activities. This study uses primary and secondary data with qualitative descriptive analysis. This study uses banking theory to determine the development of national Islamic foreign exchange banks in Indonesia. The data used are assets, liabilities, equity, and profit and loss. The total number of active national Islamic foreign exchange banks in Indonesia is 6 banks. The regulator encourages an increase in the role of national Islamic foreign exchange banks to carry out merger and acquisition strategies, hence they are strong in the capital, in BUKU IV category, can compete for business with conventional commercial banks, and can play an important role in the advancement of the Indonesian economy.